2020
DOI: 10.1186/s12917-020-02595-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of baicalin on Marek’s disease virus in CEF cells

Abstract: Background Baicalin, the main metabolic component of Scutellaria baicalensis Georgi, has various pharmacological properties including anti-inflammatory, anti-oxidant, anti-apoptotic, anti-bactericidal and anti-viral. The purpose of this study was to investigate the anti-Marek’s disease virus (MDV) activities of baicalin in CEF cells. Results Here, we showed that baicalin could inhibit viral mRNA, protein levels and overall plaque formation in a time-dependent manner. We also found that baicalin could consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…As a traditional Chinese herbal medicine, Scutellariae Radix exhibits important effects in the treatment of various diseases, including emesis, hepatitis and high blood pressure. Baicalin, the main bioactive ingredient in Scutellariae Radix, exerts antidepressant ( 21 ), anti-inflammatory and antioxidant effects ( 22 ). Therefore, baicalin content is determined for quality control of many traditional Chinese medicines containing Scutellariae Radix ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional Chinese herbal medicine, Scutellariae Radix exhibits important effects in the treatment of various diseases, including emesis, hepatitis and high blood pressure. Baicalin, the main bioactive ingredient in Scutellariae Radix, exerts antidepressant ( 21 ), anti-inflammatory and antioxidant effects ( 22 ). Therefore, baicalin content is determined for quality control of many traditional Chinese medicines containing Scutellariae Radix ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to study the mechanism of LiCl inhibition on MDV infection, three time points related to the addition of LiCl (P1: before MDV (1000 pfu) infection, P2: during MDV infection, and P3: after MDV infection) were used, similar to our previous report [21]. The results of real-time PCR and plaque counts showed that the application of 20 mM LiCl had a significant inhibitory effect on MDV replication at all time points (Figure 3).…”
Section: Inhibitory Effect Of Licl Occurs Throughout Virus Replicationmentioning
confidence: 99%
“…In order to study the mechanisms of LiCl inhibition of the virus, experiments related to the time of addition of LiCl were carried out as described previously [21]. Briefly, in the first experimental protocol (P1), CEF cells were pretreated with LiCl (20 mM) at 37 • C for 2 h, and the medium containing LiCl was removed before inoculation of 1000 PFU of virus.…”
Section: The Effect Of Different Models Of Drug Treatmentmentioning
confidence: 99%
See 2 more Smart Citations